2013
DOI: 10.1111/liv.12397
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing treatment for HCV genotype 4: PEG‐IFN alfa 2a vs. PEG‐IFN alfa 2b; the debate continues

Abstract: Hepatitis C virus (HCV) remains one of the leading causes of morbidity and mortality worldwide. Combined therapy with pegylated interferon (PEG‐IFN) and ribavirin is the current standard of care treatment for HCV genotype 4. Two types of PEG‐IFN are commercially available. The limited number of trials that were conducted for HCV genotype 4 and the few head to head comparisons make it impossible to know which is the best option? In this article we review all available PEG‐IFN trials performed worldwide for HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…Treatment of HCV is considered very important issue as it reduces the risk of decompensated liver cirrhosis and hepatocellular carcinoma hence reducing the morbidity and mortality [20]- [22]. In Egypt, PEG-IFN and RBV were introduced by ministry of health through a national treatment program for patients with chronic HCV infection since 2006, SVR rates ranged from 54% to 59% [23] [24]. The recent approval of DAAs for treatment of HCV-4 promises significant improvement in the outcome of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of HCV is considered very important issue as it reduces the risk of decompensated liver cirrhosis and hepatocellular carcinoma hence reducing the morbidity and mortality [20]- [22]. In Egypt, PEG-IFN and RBV were introduced by ministry of health through a national treatment program for patients with chronic HCV infection since 2006, SVR rates ranged from 54% to 59% [23] [24]. The recent approval of DAAs for treatment of HCV-4 promises significant improvement in the outcome of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Annually, 4000050000 patients have been treated, and 350000 patients had received therapy in this program by 2013 [150] . SVR rates for patients treated with the original PEGIFNα2a and alfa2b were 54%59% [151,152] and response rates to a locally produced biosimilar PEG IFN were reported at 52% [153] .…”
Section: Background In Hcv Treatmentmentioning
confidence: 99%
“…The type of interferon either alpha 2a or alpha 2b as a predictor of response was a point of debate most of the time [12]. In this study, we found that there was no statistical significance between patients who had either type of Interferon and their treatment outcome.…”
Section: Discussionmentioning
confidence: 52%